THE BEOTHUKA TERRANOVA (RADIOLARIA) ASSEMBLAGE AND ITS IMPORTANCE FOR THE UNDERSTANDING OF EARLY ORDOVICIAN RADIOLARIAN EVOLUTION - Maletz J.; Bruton D.L. (My University, 2005)
The radiolarian Beothuka terranova occurs in the Arenigian Didymograptellus bifidus Biozone (uppermost Lower Ordovician) of Spitsbergen (Svalbard), associated with a diverse and well-preserved radiolarian fauna. The presence of typical Cambrian spicular radiolarians associated with derived spherical forms shows a gradational faunal change from the Cambrian to the Ordovician. The genus and species Antygopora ordovicica n. gen. et n. sp. is described.
Keywords: ORDOVICIAN; RADIOLARIANS; SPITSBERGEN; BIOSTRATIGRAPHY; EVOLUTION; Paleozoic::Ordovician; Палеозой::Ордовикская